Clinical-economic analysis of the target therapy in severe atopic dermatitidis in adults - A. S. Kolbin; Y. M. Gomon; M. A. Proskurin; Y. E. Balikina (Izdatelstvo OKI, 2022)
Target therapy of severe atopic dermatitidis (AD) is actual because AD has a high prevalence and social-economic burden. Target therapy consists of monoclonal antibodies (dupilumab) as well as janus kinase inhibitors (upadacitinib and baricitinib). Aim. Health technology assessment of the severe AD target therapy in adults. Мaterials and methods. EASI-75 has been chosen as efficacy criterion in the clinical trial of dupilumab 300 mg every 2 weeks and upadacitinib 30 mg od during 24 weeks, indirect treatment comparison for dupilumab and baricitinib 4 mg od with odds ratio (OR) during 16 weeks has been performed. Modelling with "Tree of decision" method was made for comparable efficacy evaluation on 52-d week of the treatment. Direct medical cost has been calculated for: target and topic therapy, complications, prophylaxis of janus kinase inhibitors side effects. Budget impact analysis for janus kinase inhibitors substitution with dupilumab during 3-years horizon on 100 pts was performed. Multilateral sensitivity analyses were made for results validation. Results. Efficacy of dupilumab and upadacitinib on point 24 w were equal (EASI-75 59,5 % [95 % CI: 54,4; 64,7] and 64,2 % [95 % CI: 59,1; 69,2] accordingly) and on 52 w (65,0 % and 69,0 %, OR vs dupilumab 1,1 [95 % CI: 0,68; 2,1]). Dupilumab has more efficacy than baricitinib on 16 w of therapy (EASI75 65,7 % and 48,0 % accordingly, OR 2,09 [95 % CI: 1,31; 3,35]) and on 52 w (65,0 % and 55,7%, OR vs dupilumab 0,75 [95% CI: 0,47; 0,96]). Dupilumab had economic advantages on 21 % vs upadacitinib during year (993 495 Rub. and 1 253 164 Rub. per patient accordingly based on cost-minimization analysis). Dupilumab was on 11,8 % more economic vs baricitinib based on cost-effective analysis during one year of therapy also. Substitution of janus kinase inhibitors on dupilumab can lead to budget saving on 18,1-44,9 % during 3 years. Results were confirmed by sensitivity analyses. Conclusion. Health Technology of the severe AD treatment in adults with dupilumab is an economic proved.